Genetic and Molecular Characteristics of X-Ray-Sensitive Mutants of Escherichia coli Defective in Repair Synthesis - Kato, Takesi (1970)
Alleles responsible for X-ray-sensitive characteristics of three mutants of Escherichia coli B, which were also sensitive to ultraviolet (UV) irradiation, were mapped near metE locus, and named res-1, res-2, and res-3. All the res(−) mutants showed no host cell reactivability (Hcr(−)) for transducing deoxyribonucleic acid (DNA) of P1 phage irradiated by UV but they were Hcr(+) for infective DNA of P1 phage. Furthermore, they showed no detectable activity of DNA polymerase. Characteristics of allele res-1 were studied in detail. The mutant res-1 uvr(+) showed an extensive degradation of DNA after UV irradiation. Double mutants carrying res-1 uvrA(−), res-1 uvrB(−), and res-1 uvrC(−) showed no marked increase in UV sensitivity beyond that of the uvr(−) single mutants and only negligible UV-induced DNA degradation. The uvr(−) mutations showed no such suppressive effect on DNA degradation induced by X rays in these double mutants. It is concluded that res(−) mutants are defective in the second step (repair synthesis) of the excision repair process and that DNA polymerase is partly responsible for the assumed resynthesis step.